Vertical price transmission in the white teff market in Ethiopia. Issue 2 (3rd April 2019) - Sassi, Maria; Abera Mamo, Yonas
ABSTRACT: The paper contributes to the scant literature on vertical price transmission between farmers and retailers in the white teff market in Ethiopia, investigating the features of this phenomenon across the most important production regions. Using Vector Error Correction and Threshold Vector Error Correction models, our study complements the traditional investigations of linear vertical integration with the analysis of possible asymmetries in price transmission. We adopted monthly retail price series from July 2004 until January 2014. The retail price allowed us a better understanding of how an inefficient market system taxes consumers than did the wholesale price normally used in the literature. We found a low speed of vertical price co-integration for white teff with different features at the regional level. Our results show linear or symmetric price transmission for the Amhara and Southern Nations, Nationalities, and People's Region regions, revealing the relative efficiency and competitiveness of the market. On the other hand, we found the presence of non-linear price transmission for the Oromia and Tigrai regions; this asymmetry result pronounced towards positive price shocks implying a persistent price rise that worsens the livelihood of final users. Based on our findings, we suggest, among other measures, providing better market infrastructure, encouraging market participation for the product, introducing and disseminating cultures and institutions that bring producers and sellers closer, increasing the productivity of producers and the supply of their produce, and strengthening farmers' organisation as measures of policy intervention to enhance efficiency and competitiveness of the white teff supply chain in Ethiopia.